METHODS OF USING POWER POINT PROGRAMS TO MAKE THE INTERSECTION LINE OF TWO POLYGONS LOCATED IN A SPECIAL SITUATION - J. Kholiqov; Sh. Egamova (Modern American Journals, 2025)
The article provides information about the application of information technology and its effectiveness in the field of drawing geometry and engineering drawing. According to the results of the analysis, the practice of using the Power Point program during the teaching of drawing geometry showed the feasibility of using graphic programs as a part of primary graphic education in technical higher education institutions.
Keywords: Power Point, technology, multiplicity, Presenter, Apple Macintosh, projection, Ananev grid.